The usefulness of the magnetic susceptibility of loess paleosol sequences for paleoclimate and stratigraphic studies: The case of the Quaternary Palouse loess, northwestern United States - Nicholas E. Bader; Elliot A. Broze; Molly A. Coates; McKenzie M. Elliott; Gabriella E. McGann; Sarah Strozyk; Russell F. Burmester (Quaternary International, 2024)

Shell disease syndromes of decapod crustaceans - Andrew F. Rowley; Christopher J. Coates (Environmental Microbiology, 2023)
The term shell disease subsumes a number of debilitating conditions affecting the outer integument (the carapace) of decapod crustaceans, such as lobsters and crabs. Herein, we seek to find commonality in the aetiology and pathology of such conditions, and those cases that result in the progressive erosion of the cuticle through to the visceral tissues by a cocktail of microbial‐derived enzymes including lipases, proteases and chitinases. Aquimarina spp. are involved in shell disease in many different crustaceans across a wide geographical area, but the overall view is that the condition is polymicrobial in nature leading to dysbiosis within the microbial consortium of the damaged cuticle. The role of environment, decapod behaviour and physiology in triggering this disease is also reviewed. Finally, we provide a conceptual model for disease aetiology and suggest several avenues for future research that could improve our understanding of how such factors trigger, or exacerbate, this condition.

Invasive slipper limpets (Crepidula fornicata) act like a sink, rather than source, of Vibrio spp. - Emma A. Quinn; Sophie H. Malkin; Jessica E. Thomas; Ryan Poole; Charlotte E. Davies; Andrew F. Rowley; Christopher J. Coates (Biological Invasions, 2022)
A large knowledge gap exists regarding the disease profile and pathologic condition of the invasive, slipper limpet Crepidula fornicata . To help address this, we performed a year-long health survey at two sites in South Wales, UK – subtidal Swansea Bay and intertidal Milford Haven. In total, 1,800 limpets were screened systematically for haemolymph bacterial burdens using both general and vibrio-selective growth media (TSA + 2% NaCl and TCBS, respectively), haemolymph (blood) inspection using microscopy, a PCR-based assay targeting Vibrio spp., and multi-tissue histology. Over 99% of haemolymph samples contained cultivable bacterial colony-forming units, and 83% of limpets tested positive for the presence of vibrios via PCR (confirmed via Sanger sequencing). Vibrio presence did not vary greatly between sites, yet a strong seasonal effect was observed with significantly higher bacterial loads during the summer. Binomial logistic regression models revealed larger (older) limpets were more likely to harbour vibrios, and the growth of bacteria on TCBS was a key predictor for PCR-based vibrio detection. Histological assessment of > 340 animals revealed little evidence of inflammation, sepsis or immune reactivity despite the gross bacterial numbers. We contend that slipper limpets are not highly susceptible to bacteriosis at either site, and do not harbour vibrios known to be pathogenic to humans. The lack of susceptibility to local pathogenic bacteria may explain, in part, the invasion success of C. fornicata across this region.

Local Climate Conditions Shape the Seasonal Patterns of the Diptera Community in a Tropical Rainforest of the Americas - Vicente Hernández-Ortiz; José F. Dzul-Cauich; Martha Madora; Rosamond Coates (Neotropical Entomology, 2022)

Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - John Thompson; Mark A. Weaver; Ingrid Lupatsch; Robin J. Shields; Sue Plummer; Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be an approach for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio ( Listonella ) anguillarum , Vibrio alginolyticus , and V. harveyi , using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum , and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (> 100°C) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH; however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp ( Penaeus vannamei)— identified tentatively as Carnobacterium maltaromaticum . This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and reduced shrimp survival at a dose of 1 × 10 7 bacteria/shrimp. During a 28-day feeding trial, juvenile P. vannamei fed with L. plantarum supplemented diets showed no gross changes in growth parameters compared with the control. We suggest that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.

Emerging Diseases and Epizootics in Crabs Under Cultivation - Christopher J. Coates; Andrew F. Rowley (Frontiers in Marine Science, 2022)
While most crab production for human consumption worldwide comes from capture fisheries, there is increasing production of selected species using aquaculture-based methods. This is both for the purpose of stock replacement and direct yield for human consumption. Disease has limited the ability to produce larval crabs in commercial hatcheries and this together with suitable feeds, are major hurdles in the sustainable development of cultivation methods. Juvenile and adult crabs are also subject to a range of diseases that can cause severe economic loss. Emerging pathogens/parasites are of major importance to crab aquaculture as they can cause high levels of mortality and are difficult to control. Diseases caused by viruses and bacteria receive considerable attention but the dinoflagellate parasites, Hematodinium spp., also warrant concern because of their wide host range and lack of control methods to limit their spread. This concise review examines the emerging diseases in several crabs that have been selected as candidates for aquaculture efforts including Chinese mitten crabs ( Eriocheir sinensis ), mud crabs ( Scylla spp.), swimming crabs ( Portunus spp.), blue crabs ( Callinectes sapidus ) and shore crabs ( Carcinus maenas ). The latter is also a prolific invasive species known to harbour diverse macro- and micro-parasites that can affect commercially important bivalves and crustaceans.

The diarrhetic shellfish-poisoning toxin, okadaic acid, provokes gastropathy, dysbiosis and susceptibility to bacterial infection in a non-rodent bioassay, Galleria mellonella - Helena Emery; William Traves; Andrew F. Rowley; Christopher J. Coates (Archives of Toxicology, 2021)
Diarrhetic shellfish-poisoning (DSP) toxins such as okadaic acid and dinophysistoxins harm the human gastrointestinal tract, and therefore, their levels are regulated to an upper limit of 160 μg per kg tissue to protect consumers. Rodents are used routinely for risk assessment and studies concerning mechanisms of toxicity, but there is a general move toward reducing and replacing vertebrates for these bioassays. We have adopted insect larvae of the wax moth Galleria mellonella as a surrogate toxicology model. We treated larvae with environmentally relevant doses of okadaic acid (80–400 μg/kg) via intrahaemocoelic injection or gavage to determine marine toxin-related health decline: (1) whether pre-exposure to a sub-lethal dose of toxin (80 μg/kg) enhances susceptibility to bacterial infection, or (2) alters tissue pathology and bacterial community (microbiome) composition of the midgut. A sub-lethal dose of okadaic acid (80 μg/kg) followed 24 h later by bacterial inoculation (2 × 10 5 Escherichia coli ) reduced larval survival levels to 47%, when compared to toxin (90%) or microbial challenge (73%) alone. Histological analysis of the midgut depicted varying levels of tissue disruption, including nuclear aberrations associated with cell death (karyorrhexis, pyknosis), loss of organ architecture, and gross epithelial displacement into the lumen. Moreover, okadaic acid presence in the midgut coincided with a shift in the resident bacterial population over time in that substantial reductions in diversity (Shannon) and richness (Chao-1) indices were observed at 240 μg toxin per kg. Okadaic acid-induced deterioration of the insect alimentary canal resembles those changes reported for rodent bioassays.

Examining the relationship between arterial stiffness and swim-training volume in elite aquatic athletes - Christian P. Cheung; Alexandra M. Coates; Katharine D. Currie; Trevor J. King; Margo L. Mountjoy; Jamie F. Burr (European Journal of Applied Physiology, 2021)

Blood flow restriction in the presence or absence of muscle contractions does not preserve vasculature structure and function following 14–days of limb immobilization - Jeremy N. Cohen; Joshua T. Slysz; Trevor J. King; Alexandra M. Coates; Robert T. King; Jamie F. Burr (European Journal of Applied Physiology, 2021)

Rodent suppression of seedling establishment in tropical pasture - Crystal A. Guzmán; Henry F. Howe; David H. Wise; Rosamond I. Coates; Jenny Zambrano (Oecologia, 2021)

Cardiac autonomic recovery following traditional and augmented remote ischemic preconditioning - William N. Morley; Alexandra M. Coates; Jamie F. Burr (European Journal of Applied Physiology, 2021)

Prediction of plant water status in almond and walnut trees using a continuous leaf monitoring system - R. Dhillon; F. Rojo; S. K. Upadhyaya; J. Roach; R. Coates; M. Delwiche (Precision Agriculture, 2019)

Indomethacin-induced gut damage in a surrogate insect model, Galleria mellonella - Helena Emery; Richard Johnston; Andrew F. Rowley; Christopher J. Coates (Archives of Toxicology, 2019)

Pragmatic criteria to define chronic pseudomonas aeruginosa infection among adults with cystic fibrosis - Zhe Hui Hoo; Elizabeth Coates; Chin Maguire; Hannah Cantrill; Nadia Shafi; Edward F. Nash; Angela McGowan; Stephen J. Bourke; William G. Flight; Thomas V. Daniels; Julia A. Nightingale; Mark I. Allenby; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Colletotrichum species associated with pre-and post-harvest diseases of avocado and mango in eastern Australia - F. R. Giblin; Y. P. Tan; R. Mitchell; L. M. Coates; J. A. G. Irwin; R. G. Shivas (Australasian Plant Pathology, 2018)

High density brood of Australian gall-inducing Acacia thrips aid in fungal control - Peterson J. Coates; Adam Stow; Christine Turnbull; Andrew Beattie; Christopher F. Hammill; Thomas W. Chapman (Evolutionary Ecology, 2017)

Differences in carbon source utilisation by orchid mycorrhizal fungi from common and endangered species of Caladenia (Orchidaceae) - S. Mehra; P. D. Morrison; F. Coates; A. C. Lawrie (Mycorrhiza, 2017)

Scena propylea (Druce) (Lepidoptera: Erebidae) an Endemic Species of Mexico - F Hernández-Baz; R Coates; J A Teston; J M González (Neotropical Entomology, 2013)

Neogene reef coral assemblages of the Bocas del Toro region, Panama: the rise of Acropora palmata - J. S. Klaus; D. F. McNeill; A. F. Budd; A. G. Coates (Coral Reefs, 2012)

Geographic distribution of phylogenetically-distinct legume pod borer, Maruca vitrata (Lepidoptera: Pyraloidea: Crambidae) - Venu M. Margam; Brad S. Coates; Malick N. Ba; Weilin Sun; Clementine L. Binso-Dabire; Ibrahim Baoua; Mohammad F. Ishiyaku; John T. Shukle; Richard L. Hellmich; Fernando G. Covas; Srinivasan Ramasamy; Joel Armstrong; et al. (Molecular Biology Reports, 2011)

“He said, she said”: who should speak for households about experiences of food insecurity in Bangladesh? - Jennifer C. Coates; Patrick Webb; Robert F. Houser; Beatrice Lorge Rogers; Parke Wilde (Food Security, 2010)

Pathogenic diversity of avocado and mango isolates of Colletotrichum gloeosporioides causing anthracnose and pepper spot in Australia - F. R. Giblin; L. M. Coates; J. A. G. Irwin (Australasian Plant Pathology, 2010)

The epidemiology of triple-negative breast cancer, including race - Katrina F. Trivers; Mary Jo Lund; Peggy L. Porter; Jonathan M. Liff; Elaine W. Flagg; Ralph J. Coates; J. William Eley (Cancer Causes & Control, 2009)

Influence of Mouthpiece Geometry on the Aerosol Delivery Performance of a Dry Powder Inhaler - Matthew S. Coates; Hak-Kim Chan; David F. Fletcher; Herbert Chiou (Pharmaceutical Research, 2007)

Effects of rootstock and nitrogen fertiliser on postharvest anthracnose development in Hass avocado - S. L. Willingham; K. G. Pegg; J. M. Anderson; A. W. Cooke; J. R. Dean; F. R. Giblin; L. M. Coates (Australasian Plant Pathology, 2006)

Influence of Air Flow on the Performance of a Dry Powder Inhaler Using Computational and Experimental Analyses - Matthew S. Coates; Hak-Kim Chan; David F. Fletcher; Judy A. Raper (Pharmaceutical Research, 2005)

The Role of Capsule on the Performance of a Dry Powder Inhaler Using Computational and Experimental Analyses - Matthew S. Coates; David F. Fletcher; Hak-Kim Chan; Judy A. Raper (Pharmaceutical Research, 2005)

Disease resistance: a benefit of sociality in the dampwood termite Zootermopsis angusticollis (Isoptera: Termopsidae) - Rebeca B. Rosengaus; Amy B. Maxmen; Laran E. Coates; James F. A. Traniello (Behavioral Ecology and Sociobiology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Geovibrio ferrireducens , a phylogenetically distinct dissimilatory Fe(III)-reducing bacterium - F. Caccavo Jr.; John D. Coates; Ramon A. Rossello-Mora; Wolfgang Ludwig; Karl Heinz Schleifer; Derek R. Lovley; Michael J. McInerney (Archives of Microbiology, 1996)